Strategy, Lane, And Promotion Administrative In Administrating New College Students In Marime Academy Sapta Samudra Padang - Marjohan, Marjohan; Lukman, Mustika; Dedi, Dedi (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2025)
This research is qualaitative research by designing phenomenon research. The aim of the research is to describe how the strategy, lane and promotion administrative in administrating the new college students in Marime Academy Sapta Samudra Padang. The information got from four seaman lectures, four institution lecturers, BAAK and two other staffs. The technique of collecting information by using samling purposive. Technique of data collection is interview, observation, and documentation. Technique of data analysis is data collection, data reduction, data presentation and conclution. The result of research is to describe that the strategy in administrating new college students was good enough in Marime Academy Sapta Samudra Padang. The strategy involved media social, brochure, calender, banner, wall watch, umbrella which have martime logo on them, and come to school by inviting two college students. The lane of administrating new college students and administration was not good enough, because the lane of administrating new college students still found without testing and extra or addition time. Meanwhile, the administration was not complete, such as there is no permission letter, can’t get permission from the school, limited time, no committee and meeting. So, college students got confused when they follow the school visiting. Abstrak. Jenis penelitian ini adalah penelitian kualitatif dengan rancangan penelitian fenomenologi. Tujuan penelitian ini adalah untuk mengungkap bagaimana strtegi, jalur, dan administrasi promosi penerimaan mahasiswa di akademi maritim Sapta Samudra Padang. Adapun informasi dalam penelitian ini adalah 4 orang dosen pelaut, 4 orang dosen tetap, Ka. BAAK, dan 2 orang staf lainnya. Teknik pemilihan informan menggunakan purposive sampling. Teknik pengumpulan data adalah dengan wawancara, obsevasi,dan dokumentasi. Teknik analisis data yang digunakan anatara lain: pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil Penelitian ini adalah untuk strategi promosi penerimaan mahasiswa baru di Akademi Maritim Sapta Samudra Padang sudah cukup baik melalui media social, brosur, kalender, spanduk, jam dinding, payung berlogo kampus dan sosialisasi langsung ke sekolah dengan melibatkan 2 orang mahasiswa aktif. Untuk jalur penerimaan mahasiswa dan admiistrasi belum cukup baik karena pada jalur penerimaan masih ditemukan calon mahasiswa tanpa tes yang terjadual serta banyaknya perpananjangan waktu penerimaan mahasiswa baru, sedangkan administrai banyak ditemukan kekurangan antara lain: tidak mengirimkan surat, tidak dapat izin dari sekolah, waktu yang pendek, tidak ada kepanitiaan dan tidak dirapatkan, terjadinya tumpang tindih antara sesama siswa yang ikut dalam kunjungan kesekolah